The role of ethnicity and socioeconomic status in Southeast Asian mothers' parenting sensitivity. Issue 1 (2nd January 2018) - Heng, Jeremy; Quan, Jeffry; Sim, Lit Wee; Sanmugam, Shamini; Broekman, Birit; Bureau, Jean-François; Meaney, Michael J.; Holbrook, Joanna D.; Rifkin-Graboi, Anne
ABSTRACT: Past research indicates that socioeconomic status (SES) accounts for differences in sensitivity across ethnic groups. However, comparatively little work has been conducted in Asia, with none examining whether ethnicity moderates the relation between SES and sensitivity. We assessed parenting behavior in 293 Singaporean citizen mothers of 6-month olds (153 Chinese, 108 Malay, 32 Indian) via the Maternal Behavioral Q-Sort for video interactions. When entered into the same model, SES ( F (1, 288) = 17.777, p  < .001), but not ethnicity, predicted maternal sensitivity ( F (2, 288) = .542, p  = .582). However, this positive relation between SES and sensitivity was marginally moderated by ethnicity. SES significantly positively predicted sensitivity in Chinese, but not Malay dyads. Within Indian dyads, SES marginally positively predicted sensitivity only when permanent residents were included in analyses. We discuss the importance of culture on perceived SES-associated stress. However, because few university-educated Malays participated, we also consider whether university education, specifically, positively influences sensitivity.